L’odeur comme vecteur des épizooties et la mithridatisation des chevaux - Valérie Gitton-Ripoll (Pallas, 2018)
Glanders (morbus, suspirium) is a horse’s disease which was supposed to be transmitted by the breath of ill horses or emanations from dead animals in Mulomedicina Chironis 191-194. It was thus necessary to bury the cadavers, and fill the still healthy animals with perfumes of fumigation, to avoid contagion. This operation was called stagnare (equum), and it was a metaphor from metallurgic language. Gallic bronze-smith of Alesia, according to Pliny the Elder, 34, 162, covered the bronze-cauldron with pewter (stannum), to avoid oxidation: so, breathing the perfumed smoke immunizes the horses against the bad smell of glanders, like the human mithridatization by potions.